Development of a Web-Based Information System for Community Aspirations and Complaints in Bungatan Village, Bungatan District, Situbondo Regency - Muhammad Faidhurrahman Wahid; Achmad Baijuri; Firman Santoso (International Journal Software Engineering and Computer Science (IJSECS), 2026)
Web-based information systems can support the management of public services by providing more structured access to information and reports. This study aims to design and implement a web-based Community Aspiration and Complaint Information System in Bungatan Village, Bungatan District, Situbondo Regency. The existing process for submitting aspirations and complaints was still conducted manually through face-to-face communication or messaging applications, resulting in less structured data management and limited transparency in report monitoring. Data were collected through observation, interviews, documentation, and literature studies. System development followed the Waterfall method, consisting of requirements analysis, system design, implementation, testing, deployment, and maintenance. The system was developed using the CodeIgniter 4 framework with PHP and MySQL. The results show that the system enables the community to submit aspirations and complaints online and monitor report statuses through the website. Black-box testing was conducted on six main features: registration, login, complaint submission, aspiration submission, complaint management, and report status monitoring. All tested features functioned as expected based on the defined test scenarios. The system also provides centralized data storage and structured report management, supporting the administration of community aspirations and complaints in Bungatan Village.